Tacit Knowledge Sharing Among Baristas in the Coffee Shop Industry: A Qualitative Case Study at De Ngokow Coffee Roastery & Tea Club - Muh. Abdul Hadi Hasan; Murniady Muchran (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to explore the mechanisms of tacit knowledge sharing among baristas in micro, small, and medium enterprises (MSMEs) in the food and beverage sector in Indonesia. The study used a qualitative approach with a case study design at de Ngokow Coffee Roastery & Tea Club in Yogyakarta. Data were obtained through semi-structured interviews and open-ended questionnaires with 14 baristas, then analyzed using thematic analysis to identify patterns of knowledge sharing and organizational learning. The results showed that experiential learning is the primary means of barista skill acquisition, particularly related to sensory abilities, brewing techniques, and customer service. Tacit knowledge transfer occurs predominantly through senior-junior mentoring, direct observation, and informal interactions in the workplace. The study also found that high employee turnover risks the loss of organizational knowledge due to the lack of a structured knowledge documentation system. These findings emphasize the importance of developing mentoring programs, visual documentation, and employee retention strategies to maintain the sustainability of competencies in MSMEs in the food and beverage sector. This study provides an empirical contribution to the study of knowledge management in the hospitality industry and MSMEs in Indonesia.